Leadership plain and simple - Radcliffe, Steve (New York Pearson, 2012)
Leadership isn?t complicated ? keep it simple and make it count. This new edition of Steve Radcliffe?s uniquely powerful, successful and practical framework will show you how to develop faster as a more confident and capable leader.
Includes bibliographical references and index.
Keywords: Leadership